II Latin American Conference on Bioimpedance 2nd CLABIO,Montevideo,September 30 - October 02, 2015 - Simini, Franco; Bertemes-Filho, Pedro; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This volume presents the proceedings of CLABIO 2015 - II Latin American Conference on Bioimpedance, held in Montevideo, Uruguay - September 30 - October 02, 2015. The works cover a broad range in Biomedical Engineering and Computing, Medical Physics and Medical Sciences, Environment, Biology and Chemistry. The topics are: ·Bioimpedance Applications ·Bioimpedance Instrumentation ·Body and Tissue Composition ·Cell Culture and Cell Suspension ·Electrical Impedance Tomography ·Electrode Modelling ·Magnetic Induction - Electrical Impedance Tomography ·Magnetic Resonance - Electrical Impedance Tomography ·Nonlinear Phenomena ·Organ and Tissue Impedance ·Plant Tissue Impedance ·Skin Impedance Modelling ·Technological Advances in Bioimpedance ·Theory and Modelling.
Keywords: Biomedical engineering; Medical physics; Radiology; Biomedical Engineering and Bioengineering; Medical Physics; Radiology